2009
DOI: 10.1287/serv.1.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Using Survey Data to Design a RFID Centric Service System for Hospitals

Abstract: The continuous growth of health care services expenses urges U.S. government to take actions. The adoption of Information Technology, and especially RFID (Radio Frequency IDentification) allow hospitals to re-engineer their processes in order to reduce costs, maintaining the same level of service to the patients. Information technology represents a core element of the service itself; therefore a service design approach is believed to improve the adoption rate of RFID in hospitals. The main goal of the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…RFID applications can be grouped under three categories: asset control and management, people monitoring, and asset and people integration (Mogre, Gadh, & Chattopadhyay, 2009). Some of the reported benefits of RFID are: reduced amount of rental, lost or stolen equipment, reduced time spent locating missing equipment, optimized inventory levels and better managed consignment stock, expired products and recall notifications with RFID, reduce shrinkage and ensure high-value items do not expire before use (Reyes et al, 2012).…”
Section: Rfid Benefitsmentioning
confidence: 99%
See 3 more Smart Citations
“…RFID applications can be grouped under three categories: asset control and management, people monitoring, and asset and people integration (Mogre, Gadh, & Chattopadhyay, 2009). Some of the reported benefits of RFID are: reduced amount of rental, lost or stolen equipment, reduced time spent locating missing equipment, optimized inventory levels and better managed consignment stock, expired products and recall notifications with RFID, reduce shrinkage and ensure high-value items do not expire before use (Reyes et al, 2012).…”
Section: Rfid Benefitsmentioning
confidence: 99%
“…Financial concerns, such as funding and cost were usually rated highest. Fosso Wamba et al (2013) reported that the most highly published RFID-enabled healthcare issues are related to data management, security and privacy issues (Bunduchi, Weisshaar, & Smart, 2011;Fosso Wamba et al, 2008;Li, Godon, & Visich, 2010;Matta et al, 2012;Mogre et al, 2009;Vijayaraman & Osyk, 2006;Yao et al, 2012).…”
Section: Rfid Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fosso Wamba et al (2008) concluded that (1) the RFID-EPC network can improve the ''shipping', 'receiving', and 'put-away' processes, (2) these technologies can cancel, automate, or automatically trigger some business processes, (3) they foster a higher level of information sharing/ ynchronisation between supply chain members and (4) they require being integrated into a wider strategy. Mogre et al (2009) studied the introduction of RFID systems in healthcare services. The authors argue that RFID technology allows the healthcare service providers to reengineer their processes in order to reduce costs, maintaining the same level of service to the patients.…”
Section: Literature Reviewmentioning
confidence: 99%